2015
DOI: 10.1111/all.12575
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to immunotherapy are associated with different patterns of sensitization to grass allergens

Abstract: The aim of the study was to investigate whether adverse drug reactions (ADRs) during immunotherapy with a grass extract (AVANZ® Phleum, ALK-Abelló) are related to the different patterns of sensitization of patients to grass allergens. A total of 192 patients with rhinitis and/or asthma sensitized to grass pollen received a 4-week updosing with five injections. ADRs were evaluated following EAACI guidelines. A total of 432 ADRs in 133 (69%) patients were recorded, 64% local and 31% systemic. There was a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…In fact, a recent study conducted in Italy showed that 23% of pollen-sensitized patients had IgE antibodies to profilins [27] and frequent sensitization to cross-reactive pollen allergens has been reported for many countries such as the southern parts of Europe [7,21,28,29]. In fact, patients in Astana, Kazakhstan, are exposed simultaneously to pollen from several unrelated plant species due to a short summer period with copollination of trees, grasses, and weeds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study conducted in Italy showed that 23% of pollen-sensitized patients had IgE antibodies to profilins [27] and frequent sensitization to cross-reactive pollen allergens has been reported for many countries such as the southern parts of Europe [7,21,28,29]. In fact, patients in Astana, Kazakhstan, are exposed simultaneously to pollen from several unrelated plant species due to a short summer period with copollination of trees, grasses, and weeds.…”
Section: Discussionmentioning
confidence: 99%
“…In an allergen study involving subcutaneous immunotherapy with an accelerated schedule, profilin-sensitized patients showed higher specific IgE levels to major grass allergens and a higher probability of suffering from systemic side effects, particularly late-phase urticarial reactions [6]. All of these findings support the idea that profilin sensitization and profilin hypersensitivity prevalence in a particular area have the potential to predict the allergic inflammation level associated with grass pollinosis.…”
mentioning
confidence: 72%
“…The molecular-based diagnosis would certainly improve the accuracy in AIT prescription [22, 123, 124], allowing to dissect the genuine sensitizations and the cross-reactions due to pan-allergens. The epicutaneous and intralymphatic routes of administration would represent an intriguing prospective approach, especially in the pediatric age [27].…”
Section: The Unmet Needs and The Future Directionsmentioning
confidence: 99%